1999
DOI: 10.1021/om980904h
|View full text |Cite
|
Sign up to set email alerts
|

Reaction of 1,2-Disilylbenzene with Bis[1,2-bis(dimethylphosphino)ethane]nickel(0). Isolation and Characterization of the First Silylnickel(IV) Complex

Abstract: The first silylnickel(IV) complex was isolated from the reaction of 1,2-disilylbenzene with a nickel(0) complex and characterized by multinuclear NMR and X-ray structure analysis. Bis(silyl)nickel(II) complexes, intermediates in the formation of the silylnickel(IV) complex, were also characterized by NMR and/or X-ray analysis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

2
28
0
5

Year Published

2001
2001
2019
2019

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 70 publications
(35 citation statements)
references
References 10 publications
2
28
0
5
Order By: Relevance
“…[9] a disproportionation reaction at the Ni II stage is sufficient, while the silyl nickel compound 3 [10] is generated by a thermally induced elimination of dihydrogen. In a similar modification for the synthesis of the distorted tetrahedral norbornyl nickel 4 [11] oxidation by air at À60 8C is sufficient.…”
mentioning
confidence: 99%
“…[9] a disproportionation reaction at the Ni II stage is sufficient, while the silyl nickel compound 3 [10] is generated by a thermally induced elimination of dihydrogen. In a similar modification for the synthesis of the distorted tetrahedral norbornyl nickel 4 [11] oxidation by air at À60 8C is sufficient.…”
mentioning
confidence: 99%
“…We have found that sterically less demanding chelating silyl ligands are useful in stabilizing silyl transition-metal compounds with high formal oxidation states (15) and reported silylpalladium(IV) (16) and silylnickel(IV) compounds (17). During our effort to synthesize silyl group 10 transition-metal compounds with formal oxidation states exceeding ϩ4, we obtained a trinuclear Pd compound 1 (Fig.…”
mentioning
confidence: 99%
“…Bisher ist das einzige geeignete Lösungsmittel flüssiger Ammoniak, [17][18][19] [25] [{1,2-C 6 H 4 (SiH 2 )-(SiH)} 2 Ni 2 (Me 2 PCH 2 CH 2 PMe 2 ) 2 ] 2.210-2.304 , [26] [{1,2-C 6 H 4 (SiH 2 )} 2 Ni(Me 2 PCH 2 CH 2 PMe 2 )] 2.252 und 2.290 . [27] Erste quantenchemische Berechnungen des zentralen…”
Section: àunclassified